Sensitizing effect of acetylene and 1,3-butadiene on toluene oxidation in laminar flames - Keksel, Ewald; Kluge, Sebastian; Schleier, Domenik; Höner, Martin; Karakaya, Yasin; Bierkandt, Thomas; Köhler, Markus; Kasper, Tina (Combustion and Flame)

Resonance enhanced multiphoton ionization detection of aromatics formation in fuel-rich flames - Kasper, Tina; Hansen, Nils (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Investigation of the combustion chemistry in laminar, low-pressure oxymethylene ether flames (OME0–4) - Gaiser, Nina; Zhang, Hao; Bierkandt, Thomas; Schmitt, Steffen; Zinsmeister, Julia; Kathrotia, Trupti; Hemberger, Patrick; Shaqiri, Shkelqim; Kasper, Tina; Aigner, Manfred; Oßwald, Patrick; Köhler, Markus (Combustion and Flame)
Quantitative speciation data for alternative fuels is highly desired to assess their emission potential and to develop and validate chemical kinetic models. In terms of substitute choices for fossil diesel are oxymethylene ethers (OMEs) strongly discussed. Due to the absence of carbon-carbon bonds, soot emis-sions from combustion of OMEs are low, but significant emissions of unregulated pollutants such as alde-hydes emerge. The combustion behavior of OME fuels with different chain lengths, OME0-4, was investigated in lam-inar premixed low-pressure flames using complementary molecular-beam mass spectrometry (MBMS) techniques. MBMS sampling provides an in-situ access directly into the reaction zone of the flame. Al-most all chemical species involved in the oxidation process can be detected and quantified simultane-ously. Neat OME0-3 flames were analyzed by electron ionization (EI) MBMS with high mass resolution ( R approximate to 3900) providing exact elementary composition. To obtain isomer-specific information, an OME1- doped hydrogen flame and a stochiometric OME4 flame were studied by double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy. Both, EI-MBMS detection and i2PEPICO spectroscopy, en-ables a complete overview of all intermediates. The results show a dominance of oxygenated intermediates for all measured conditions. Mole fraction profiles for the most important species are presented (i.e. formaldehyde, methanol, methyl formate and formic acid) and compared to modeling results. Hydrocarbons with more than four carbon atoms were not detected under the investigated conditions. Isomers such as ethanol/dimethyl ether (m/z = 46) and ethenol/acetaldehyde (m/z = 44) could be separated using threshold photoelectron spectra for clear iden-tification and photoionization efficiency curves for quantification. This investigation permits the discus-sion and analysis of systematic trends, including intermediate species, for the combustion of the studied series of oxymethylene ether fuels. (c) 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

On the diversity of fossil and alternative gasoline combustion chemistry: A comparative flow reactor study - Zinsmeister, Julia; Gaiser, Nina; Melder, Jens; Bierkandt, Thomas; Hemberger, Patrick; Kasper, Tina; Aigner, Manfred; Köhler, Markus; Oßwald, Patrick (Combustion and Flame)
Recent progress in molecular combustion chemistry allows for detailed investigation of the intermediate species pool even for complex chemical fuel compositions, as occur for technical fuels. This study pro-vides detailed investigation of a comprehensive set of complex alternative gasoline fuels obtained from laminar flow reactors equipped with molecular-beam sampling techniques for observation of the com-bustion intermediate species pool in homogeneous gas phase reactions. The combination of ionization techniques including double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy enables deeper mechanistic insights into the underlying reaction network relevant to technical fuels. The se-lected fuels focus on contemporary automotive engine application as drop-in fuels compliant to European EN 228 specification for gasoline. Therefore, potential alternative gasoline blends containing oxygenated hydrocarbons as octane improvers obtainable from bio-technological production routes, e.g., ethanol, iso- butanol, methyl tert -butyl ether (MTBE), and ethyl tert -butyl ether (ETBE), as well as a Fischer-Tropsch surrogate were investigated. The fuel set is completed by two synthetic naphtha fractions obtained from Fischer-Tropsch and methanol-to-gasoline processes alongside with a fossil reference gasoline. In total, speciation data for 11 technical fuels from two atmospheric flow reactor setups are presented. Detailed main and intermediate species profiles are provided for slightly rich ( 4) = 1.2) and lean ( 4) = 0.8) con-ditions for intermediate to high temperatures. Complementary, the isomer distribution on different mass channels, like m/z = 78 u fulvene/benzene, of four gasolines was investigated. Experimental findings are analyzed in terms of the detailed fuel composition and literature findings for molecular combustion chemistry. Influences of oxygenated fuel components as well as composition of the hydrocarbon frac-tions are examined with a particular focus on the soot precursor chemistry. This dataset is available for validation of chemical kinetic mechanisms for realistic gasolines containing oxygenated hydrocarbons.(c) 2021 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Nitrous acid in high-pressure oxidation of CH4 doped with nitric oxide: Challenges in the isomer-selective detection and quantification of an elusive intermediate - Hoener, Martin; Kasper, Tina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Aluminum Diethylphosphinate as a Flame Retardant for Polyethylene: Investigation of the Pyrolysis and Combustion Behavior of PE/AlPi-Mixtures - Lau, S.; Gonchikzhapov, M.; Paletsky, A.; Shmakov, A.; Korobeinichev, O.; Kasper, Tina; Atakan, B. (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

On the diversity of fossil and alternative gasoline combustion chemistry: A comparative flow reactor study - Zinsmeister, Julia; Gaiser, Nina; Melder, Jens; Bierkandt, Thomas; Hemberger, Patrick; Kasper, Tina; Aigner, Manfred; Köhler, Markus; Oßwald, Patrick (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Dimethyl ether (DME) and dimethoxymethane (DMM) as reaction enhancers for methane: Combining flame experiments with model-assisted exploration of a polygeneration process - Zhang, Hao; Kaczmarek, Dennis; Rudolph, Charlotte; Schmitt, Steffen; Gaiser, Nina; Oßwald, Patrick; Bierkandt, Thomas; Kasper, Tina; Atakan, Burak; Kohse-Höinghaus, Katharina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Experimental and numerical study of polyoxymethylene (Aldrich) combustion in counterflow - Glaznev, Roman K.; Karpov, Alexander I.; Korobeinichev, Oleg P.; Bolkisev, Andrei A.; Shaklein, Artem A.; Shmakov, Andrey G.; Paletsky, Alexander A.; Gonchikzhapov, Munko B.; Kumar, Amit (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

An experimental study of horizontal flame spread over PMMA surface in still air - Korobeinichev, Oleg; Gonchikzhapov, Munko; Tereshchenko, Alexander; Gerasimov, Ilya; Shmakov, Andrey; Paletsky, Alexander; Karpov, Alexander (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Counterflow flames of ultrahigh-molecular-weight polyethylene with and without triphenylphosphate - Korobeinichev, O.P.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shundrina, I.K.; Kuibida, L.V.; Shmakov, A.G.; Hu, Y. (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry